Development/exploration funding for black junior miners in South Africa - Mazibuko, Molebogeng (Graduate School of Business (GSB), 2022)
The lack of racial transformation in most industries has led the government to craft policies geared towards distributing the pillars of power and influence of all races, especially the previously disadvantaged people of South Africa. A policy is not standalone; hence, on its own will not lead to the materialisation of any of government's plans. It is on the back of this that a solution to any problem needs to be a product of a collaborative system. In 2015, over 80% of all prospecting rights held by black owners expired and changed ownership from blacks to whites. The purpose of this research study is to investigate the proportion of black junior miners holding prospecting rights that manage to advance to obtain a mining license and then to production. Moreover, this study aims to describe and explain attributes that influence the investigated phenomenon to derive mitigations and remedies. It is assumed that since black people could participate in natural resources, economic activity post the apartheid era of the nation, the representation of blacks in this industry regarding ownership of productive assets is still less than 15%. This study uses a qualitative research methodology by examining the funding challenges experienced by black junior miners in taking their projects forward by investigating the proportion of allocated prospecting rights to blacks that reach production. A literature review was undertaken as a backbone to the phenomenon being researched. The researcher conducted qualitative research, interviewing 12 respondents; 8 of whom are middle to senior managers in their prospective companies and 4 of whom are aspiring mining owners with prospecting rights. The research findings revealed predominant themes, among which are the inefficient application process, poor quality applications, little to no government support to help execute their transformation agenda within mineral economics, limited funding allocated towards the development of early-stage mineral resources projects and the nation's deficiency of experienced early-stage funders and funding mechanics. Practical recommendations were provided, and these show a correlation between a participant-private-public relationship that needs to happen to achieve the intended purpose of the study. In absence of funding commitment from private entities, the only option the country has might be to constitute a consolidation policy, forcing majors to financially adopt juniors with a clawback option.